Competition and profit hiding: evidence from banks in China. Issue 10 (7th October 2014) - Haizhi Wang, Dr; Jin, Dawei; Liu, Jianghui; Liu, Liuling; Yin, Desheng
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the quality of financial reporting by banks in China, and the profit hiding behavior of banks in particular. Design/methodology/approach – Reported profit is compared with actual profit using multiple regression analysis. The identification strategy allows the authors to quantify the degree of profit hiding in banking institutions. Findings – Profit hiding exists in the whole banking sector in China regardless of the ownership structure of individual banks, though joint-stock banks have higher degree of profit hiding. Banks that are more financially constrained hide more profit than those less constrained ones. The competition in the banking industry competition impacts the extent of profit hiding, with higher competition being associated with lower degree of profit hiding. Research limitations/implications – This paper documents the prevailing behavior of profit hiding in Chinese banks. It raises issues regarding the conventional methods of measuring bank efficiencies using accounting information reported by banking institutions. Originality/value – This paper empirically examines the profit hiding behavior of banks in a transitional country.